When neuroglial tissue wanders: a unique case report of subpleural heterotopia in a triploid foetus and review of the literature - Procházka, Viktor; Skopelidou, Valeria; Delongová, Patricie; Hurník, Pavel; Špaček, Richard; Matura, David; Pavlíček, Jan; Gřegořová, Andrea; Vaculová, Jana; Škarda, Jozef (Frontiers in Medicine, 2025)
Heterotopic occurrence of neuroglial tissue is an exceedingly rare phenomenon with unclear pathogenesis, often presenting as lesions outside the central nervous system (CNS). We report a unique case of heterotopic neuroglial tissue identified in the thoracic cavity of a fetus aborted at 14 weeks due to a suspected Dandy–Walker malformation. The fetus exhibited neuroglial tissue growth subpleurally, alongside a suspected Dandy–Walker malformation and ventricular septal defect. While theories such as vascular embolisation, aspiration, and aberrant migration attempt to explain such occurrences, the exact etiology remains elusive. Our case suggests a potential association between triploidy and neuroglial heterotopia, supporting the aberrant migration and differentiation theory.